Effect of multi-layer prosthetic foam liner on the stresses at the stump–prosthetic interface (Fracture and Structural Integrity, 2021)
The prosthetic liner plays a significant role in the redistribution of the pressure between the stump and the socket, as it adding a cushioning layer between the stump and the socket which relieves pain and makes the prosthesis more comfortable.This study employed nonlinear finite element analyses to investigate the peak pressure and shear stress at stump–prosthetic interface in the case of multi-layer prosthetic foam liner, this liner having an inner polymeric foam layer Surrounded by another type of polymeric foam layer, we used three different types of foams in different order to define this liner (flexible polyurethane foam, polyurethane-shape memory polymer foam, and natural rubber latex foam). That’s allows comparing 6 deferent configuration of multi-layer prosthetic foam liner.
Keywords: Prosthesis; Stump; Contacts stresses; Multi-layer liner; Trans-tibial amputation